The horsemen of the Apocalypse: messianism and terror - Rogozinski, Jacob (Continental philosophy review, 2020)
I draw a phenomenological approach to religious violence by using as an example the terror apparatus called Daesh (or ISIS). After a brief reminder of my method (the egoanalysis), I analyze the schemas that underlie this apparatus, especially the schemas of the messiah and the Apocalypse, and the affects that the apparatus manages to capture. I show that messianic hope can be associated with hate through the figure of the anti-messiah—Christian Antichrist, the Dajjal of Muslims—which allows messianism to be tied to the schema of the "evil conspiracy." I finally suggest that it is possible to understand messianism differently by dissociating it from these other schemas.